IMPLEMENTASI E-MARKETPLACE KERUPUK DI DESA KALITEKUK - Ridwan, Mahfud; Ahmad Jazuli; Tutik Khotimah (Pogram Studi Sistem Komputer Universitas Serang Raya, 2024)
This research aims to develop a Kerupuk MSME application that facilitates Micro, Small and Medium Enterprises (MSMEs) in selling and buying products online. This application involves three main types of users, namely admin, seller, and buyer. This research has successfully implemented features and pages that suit the needs of each type of user, and has gone through a series of thorough blackbox tests to ensure quality and functionality. The test results show that this application functions properly and is ready for widespread use. In addition, this application is expected to increase efficiency in store management, products and orders for sellers, as well as provide a comfortable and safe shopping experience for buyers. With this application, it is hoped that it can increase the exposure and competitiveness of MSME products online, so that it can support the growth and development of MSMEs in the digital era.